2021
DOI: 10.1002/dta.3203
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of the synthetic cannabinoids ADB‐BUTINACA and ADB‐4en‐PINACA and their detection in forensic toxicology casework and infused papers seized in prisons

Abstract: Early warning systems detect new psychoactive substances (NPS), while dedicated monitoring programs and routine drug and toxicology testing identify fluctuations in prevalence. We report the increasing prevalence of the synthetic cannabinoid recep-. ADB-BUTINACA was first detected in a seizure in Sweden in 2019, and we report its detection in 13 routine Swedish forensic toxicology cases soon after. In January 2021, ADB-BUTINACA was detected in SCRA-infused papers seized in Scottish prisons and has rapidly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…To the best of our knowledge, no pharmacokinetic data for 15 (PX-1) or 19 (PX-2) in mammalian species have been reported to date. SCRAs featuring amino acid amides are subject to extensive metabolic biotransformation, 59,86,88 and it is possible that the low in vivo potency of 15 (PX-1) and 19 (PX-2) may be attributed to the rapid biotransformation of these compounds to inactive metabolites. Although 15 (PX-1) and 19 (PX-2) are closely related to several SCRAs that are potent CB 1 receptor agonists in vivo, even small changes in the molecular structure can produce vastly different metabolic profiles and clearance rates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To the best of our knowledge, no pharmacokinetic data for 15 (PX-1) or 19 (PX-2) in mammalian species have been reported to date. SCRAs featuring amino acid amides are subject to extensive metabolic biotransformation, 59,86,88 and it is possible that the low in vivo potency of 15 (PX-1) and 19 (PX-2) may be attributed to the rapid biotransformation of these compounds to inactive metabolites. Although 15 (PX-1) and 19 (PX-2) are closely related to several SCRAs that are potent CB 1 receptor agonists in vivo, even small changes in the molecular structure can produce vastly different metabolic profiles and clearance rates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Corresponding MS spectrum of GC peak with retention of 14.3 min is shown in Figure 6 a, which matches well with the standard EI spectrum of ADB-BUTINACA [ 48 ] and confirms the accuracy of test results using our portable DLIT-MS instrument. In fact, ADB-BUTINACA is a rather new synthetic cannabinoid which was first found in Europe in 2019 [ 49 ]. This case study demonstrated that by following up-to-date literature and analytical information from standard equipment, it is possible to expand the library and detect new analytes even without testing with standard samples.…”
Section: Resultsmentioning
confidence: 99%
“…Mail is one of the main reported pathways for the smuggling of drugs into prison. Reported methods for the concealment of drugs in mail include under postage stamps or labels (Godfrey, 2011; Penfold et al, 2005; Russo et al, 2019; Schweitzer et al, 2018); in the folds and glue seams of envelopes (Gearhart, 2006; Penfold et al, 2005; Schweitzer et al, 2018); in slit‐open heavy card stock such as business cards, greetings cards, and postcards (Schweitzer et al, 2018); between the pages of magazines, newspapers, or letters (Gearhart, 2006; Office of the Inspector General, 2003; Penfold et al, 2005); in the barrels of pens (Penfold et al, 2005); in the tongues or hollowed out soles of trainers (Lankenau, 2001; Penfold et al, 2005); sewn into the waistbands of clothing or linings of jackets and coats (Godfrey, 2011; Lankenau, 2001; Penfold et al, 2005); infused into paper (Antonides et al, 2020; Apirakkan et al, 2020; Caterino et al, 2019; EMCDDA, 2018; Ford & Berg, 2018; Grace et al, 2019; Gray & Ralphs, 2021; Hvozdovich et al, 2020; Kronstrand et al, 2021; Norman, McKirdy, et al, 2020; Norman, Walker, et al, 2020; Norwood, 2019; Office of the Inspector General, 2003; Ralphs et al, 2017; Rodrigues et al, 2021; Russo et al, 2019; Wakeling & Lynch, 2020); and in electrical goods (George et al, 2009; Penfold et al, 2005). For example, prisoners reported that people would place drugs inside stereos and other electrical goods along with something to block x‐rays and then send them into the prison where they would be dropped on the floor to retrieve the drugs (George et al, 2009).…”
Section: Prison Drug Smuggling Routesmentioning
confidence: 99%